Employee Company Share Owner Layoff in Indonesia: Problem and Solution from Business Judgment Rule Perspective - Suyono Musimin; Adnan Hamid; Irwansyah Irwansyah; Agung Iriantoro; Irfan Benjamin (Jurnal Mulawarman Law Review, 2025)
Indonesia protects workers who experience layoffs by providing severance pay, award money, or resolving industrial relations disputes through litigation. This study aims to map the problem and the legal solution regarding termination of employment for employees who are also shareholders in the company where they work. The research in this article employed Normative Juridical and the problem approach used in writing this research consists of two approaches: the statute approach and the conceptual approach. Share ownership by employees through Employee Stock Option Program will give employees a dual status, namely as workers and owners of the company. Termination of employment carried out by the company against shareholders is problematic. On the one hand, there is an employment relationship between the employee and the company, on the other hand, there is also a relationship between the employee as a shareholder and the company. As a civil law country, Indonesia has also adopted business judgement rule as implemented in limited liability company law, which emphasises the role and responsibilities of the company's organs and is valid until now. Business judgement rule as a guideline and instruction for the Board of Directors in making business decisions where the Board of Directors must always uphold the principles of prudence, good faith, solely for the interests of the company, subject to the provisions of the articles of association and laws and regulations.